Comparison of The Detail and Dimensional Accuracy of Duplicate Working Models Using Jelly Powder and Reversible Hydrocolloid - Suryani Catur Suprapti; Aryudhi Armis; Sepriana Urianti (Sociometry Journal of Social Science, Art and Humanity, 2022)
Making dentures requires an accurate working model of the patient's jaw impression. Reversible hydrocolloid is a jelly-based impression material (class Rhodophyceae) with high accuracy. However, it has disadvantages regarding syneresis, imbibition, and is expensive. This study aims to compare the detail and dimensions accuracy of the duplicate working model using jelly powder (JP) and reversible hydrocolloid (RH). The research used a quasi-experimental design with a sample of 24. The study was carried out at the Dental Technician Laboratory of the Politeknik Kesehatan Tanjung Karang in October 2021. The accuracy and precision of the same dimensions of the work model compared to 0 minutes, 10 minutes, and 20 minutes of delayed casting. The data analysis used univariate and bivariate (Alpha=0.05). The results showed no difference in the detailed accuracy of the working model between JP and RH. The measurement results of the mean central distance from the right M1 middle fossa to the right C cup crest (AB) (p=0.607). Similarly, the mean distance from the top of the right C cup to the top of the left C cup (BC) (p=0.793). Significant differences were found in the distance from the top left of the C cup to the right M1 central fossa (AC) (p=0.006). The study has proven that jelly powder can be used as a substitute for reversible hydrocolloids in making working models.